Contribution of improved rice varieties to poverty reduction and food security in sub-Saharan Africa - Arouna, A.; Lokossou, Jourdain C.; Wopereis, Marco C.S.; Bruce-Oliver, S.; Roy-Macauley, H. (Elsevier, 2017)
The dissemination of improved rice varieties could contribute significantly to achieving food security and reducing poverty in sub-Saharan Africa (SSA). This study assesses the number of households and individuals lifted out of poverty and food insecurity. Metadata and primary data collected from sixteen countries were analyzed. A positive impact of improved varieties on food security and poverty reduction was observed over the period 2000–2014. In addition, the rate of adoption of these varieties increased over these years and this increase was more significant after the 2008 food crisis. Average income also increased from US$ 25 capita–1 to US$ 58 capita–1 for NERICA adopters. These trends could be enhanced by addressing production constraints and certified seed bottlenecks.